A method for the digital image analysis of ceramic grains based on shape factor segmentation - De Campos, Elson [UNESP]; De Lucena, Émerson F. [UNESP]; De Melo, Francisco C.L.; De O. Hein, Luis Rogerio [UNESP] (Trans Tech Publications, 2003)
A very simple and robust method for ceramics grains quantitative image analysis is presented. Based on the use of optimal imaging conditions for reflective light microscopy of bulk samples, a digital image processing routine was developed for shading correction, noise suppressing and contours enhancement. Image analysis was done for grains selected according to their concavities, evaluated by perimeter ratio shape factor, to avoid consider the effects of breakouts and ghost boundaries due to ceramographic preparation limitations. As an example, the method was applied for two ceramics, to compare grain size and morphology distributions. In this case, most of artefacts introduced by ceramographic preparation could be discarded due to the use of perimeter ratio exclusion range.
Keywords: Ceramography; Digital image analysis; Perimeter ratio; Reflective light microscopy; Ceramic grain; Ceramographic preparation; Light imaging; Shading correction; Shape factor segmentation; Cameras; Charge coupled devices; Etching; Grain boundaries; Grain size and shape; Image analysis; Image segmentation; Light interference; Morphology; Optical filters; Optical microscopy; Ceramic materials